Mechanical Properties Of Recycled Paper And Cardboard - Dragan Obradovic; Lakshmi Narayan Mishra (The Journal of Engineering and Exact Sciences)
In flotation deinking, the released ink should also be detached from the substrate and dispersed in order to avoid redeposition. However, in flotation deinking the probability of removal of an ink containing particle is driven by a combination of size and surface energy. In flotation deinking a certain amount of agglomeration is preferable as the removal in flotation deinking is dependent on the size of the particle. The optimum size range is often stated to be between 50 and 150 micrometers. Size alone however is not additionally the agglomerates should demonstrate surface energy properties that are more hydrophobic than wash deinking in order to allow for stable attachment and transport by air bubbles. The presence of surfactant in the formulation has a higher value for the result.